Air- and Water-Stable Heteroleptic Copper (I) Complexes Bearing Bis(Indazol-1-Yl)Methane Ligands: Synthesis, Characterisation, and Computational Studies - Zúñiga-Loyola, C; Zúñiga-Loyola, C (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
A series of four novel heteroleptic Cu(I) complexes, bearing bis(1H-indazol-1-yl)methane analogues as N,N ligands and DPEPhos as the P,P ligand, were synthesised in high yields under mild conditions and characterised by spectroscopic and spectrometric techniques. In addition, the position of the carboxymethyl substituent in the complexes and its effect on the electrochemical and photophysical behaviour was evaluated. As expected, the homoleptic copper (I) complexes with the N,N ligands showed air instability. In contrast, the obtained heteroleptic complexes were air- and water-stable in solid and solution. All complexes displayed green-yellow luminescence in CH2Cl2 at room temperature due to ligand-centred (LC) phosphorescence in the case of the Cu(I) complex with an unsubstituted N,N ligand and metal-to-ligand charge transfer (MLCT) phosphorescence for the carboxymethyl-substituted complexes. Interestingly, proper substitution of the bis(1H-indazol-1-yl)methane ligand enabled the achievement of a remarkable luminescent yield (2.5%) in solution, showcasing the great potential of this novel class of copper(I) complexes for potential applications in luminescent devices and/or photocatalysis. © 2023 by the authors.